Prolonged sitting time links to subclinical atherosclerosis. Issue 1 (6th January 2022) - Lim, Su Shen; Huang, Chin-Chou; Hsu, Pai-Feng; Lin, Chung-Chi; Wang, Yuan-Jen; Ding, Yaw-Zon; Liou, Teh-Ling; Wang, Ying-Wen; Huang, Shao-Sung; Lu, Tse-Min; Chen, Jaw-Wen; Chan, Wan-Leong; et al.
Abstract : Background: This study investigates the association between daily sitting time and subclinical atherosclerosis by using coronary computed tomography angiography (CCTA). Methods: The study enrolled 203 subjects (age 57.6 ± 8.8 years) who underwent CCTA at annual medical checkups. Sitting time was categorized as < 5 hours/day (short), 5 to 9 hours/day (moderate) and ≥10 hours/d (long). We analyzed the coronary calcium score, plaque characteristics, and severity of coronary artery stenosis, including the segment involvement score (SIS) and segment stenosis score (SSS). Results: Subjects with longer sitting times tended to be male gender and have lower levels of high-density lipoprotein cholesterol ( p for trend < 0.05). In addition, those with longer sitting time had higher SIS (1.2 ± 1.5 vs. 1.6 ± 2.1 vs. 2.3 ± 2.0 for short, moderate, and long sitting time, respectively) ( p for trend = 0.015) and SSS (1.4 ± 2.0 vs. 1.9 ± 2.7 vs. 2.7 ± 2.6) ( p for trend = 0.015), suggesting longer sitting time-correlated with the severity of coronary atherosclerosis. When considering the coronary plaque patterns, subjects with shorter sitting time (<5 hours/d) tended to have more calcified plaque and subjects with longer sitting time (≥10 hours/d) had more mixed plaque ( p for trend = 0.018). After adjusting for age, gender, comorbidities, body mass index, and lipid profiles, increased sitting time was independently associated with the presence of mixed plaque, suggesting longer sitting time may be associated with higher risk of the formation of vulnerable plaque. Conclusion: Longer sitting time was linked to the severity of subclinical atherosclerosis and the presence of high-risk vulnerable plaque in the general population.